Qualitative, quantitative and genotypic evaluation of Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum isolated from individuals with different periodontal clinical conditions - Arenas Rodrigues, Viviane Aparecida; de Avila, Erica Dorigatti [UNESP]; Nakano, Viviane; Avila-Campos, Mario Julio (Elsevier, 2018)
Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum are strongly associated with periodontitis, and their evaluations are relevant to understand their role in the etiology and progression of periodontal diseases. In this study, the qualitative and quantitative detection of A. actinomycetemcomitans and F. nucleatum, as well as their genetic diversity, were evaluated in individuals with gingivitis, chronic periodontitis and periodontally healthy. In addition, the biotyping, serotyping, and prevalence of the ltx and cdt genes in A. actinomycetemcomitans were also determined. Subgingival biofilms obtained from gingivitis (70), periodontitis (75) and healthy (95) individuals were analyzed by cultures and PCR. Bacterial typing and presence of ltx and cdt genes in A. actinomycetemcomitans were also verified. DNA from A. actinomycetemcomitans and F. nucleatum was detected respectively, in 65.7% and 57.1% of gingivitis, 80% and 68% of periodontitis, and 57.8% and 37.8% of healthy. A. actinomycetemcomitans from gingivitis were biotypes I, II, IV, V, and X, and serotypes a, c, and e. In periodontitis, biotypes II, VI, and X, and serotypes a, b, and c were found. In healthy subjects, biotypes II and X, and serotypes b and c were found. The LTX and ltxA were observed in strains from gingivitis and periodontitis pockets. Subsequently, our data also showed no direct relationship between ltxA gene expression and leukotoxin gene 530-bp presence. On the other hand, cdt gene predominated during the inflammatory disease process. Our results strongly support a role of A. actinomycetemcomitans and F. nucleatum in advanced stage of periodontal disease.
Keywords: Aggregatibacter actinomycetemcomitans; Bacterial typing; Fusobacterium nucleatum; Oral microbiology; Periodontal disease